(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2016)
Introduction: Bangladesh is a developing country and the industrialization process is also getting momentum. Due to rapid industrialization and mechanization, use every day more people are coming in contact with the information technology, consequently computer use which may enhance sufferings of people by causing musculoskeletal disorders. Objective: to find out among bankers (a) the prevalence of musculoskeletal disorder and (b) the association between musculoskeletal pain and computer use. Methods: This descriptive type of cross sectional study was conducted to see the pattern of musculoskeletal disorders among the computer users in three selected banks of Dhaka city with a sample of 400. Results: More than half of the respondents (59.8%) were married, more than two-third (69.2%) was male. Majority of the respondents (58.25% and 33.0%) belonged to the level of education was graduate and post graduate. Statistically significant association found between duration of computer used in years and severity of pain. (P- Value was 0.019). Conclusion: A high proportion of Bangladeshi computer users among bankers reported musculoskeletal disorder at some body site in their occupational lives with the neck and back being injured most often. Education program on prevention and coping strategies for musculoskeletal disorders are recommended for computer users in order to reduce the rate of occupational hazards. Chatt Shi Hosp Med Coll J; Vol.15 (1); Jan 2016; Page 40-44